Analysis of the thermal stability of mercuric reductase from the hot brine environment of Atlantis II in the Red Sea by site-directed mutagenesis: Structural interpretation of thermolabile and enhanced thermostable mutants - Galal, Mohamad Maged (AUC Knowledge Fountain, 2017)
The lower convective layer (LCL) of the Atlantis II (ATII) deep brine is a unique environment located in the central Red Sea at a depth of 2000-2200 meters. It is characterized by high salinity, temperature of 68Î¿C and high concentrations of toxic heavy metals. Microbial community residing in the LCL of the Atlantis II deep brine have their cellular constituents evolutionarily adapted to their functions under these multiple environmental stressors. To cope with toxic heavy metals, such as mercury, and high temperature, microorganisms need a thermostable mercuric detoxification system. In this work, we analyze the properties of a mercuric reductase from this environment. The enzyme is a key component of the bacterial detoxification system of mercurial compounds. The gene for this enzyme was identified in a PCR-based MerA library which was established using DNA isolated from the microbial community of LCL-ATII environment and MerA-specific oligonucleotides as primers. Using a reverse genetics approach, the coding sequence of this gene was synthesized, cloned into an expression vector, protein expressed in E. coli and the recombinant MerA enzyme (named ATII-LCL-NH) was purified. In contrast to a homolog described earlier from the same environment (MerA ATII-LCL), the ATII-LCL-NH enzyme was found to be strongly inhibited by NaCl and it does not have the halophilic signature present in ATII-LCL (replacement of nonpolar amino acids with acidic residues and decrease of the hydrophobicity of the protein). These structural features of ATII-LCL-NH indicate that most probably the ATII-LCL-NH evolved in a microorganism that utilizes the compatible solutes strategy. As expected from an enzyme that efficiently functions in an environment characterized by high temperature, the ATII-LCL-NH was stable at 70oC. However, when compared with the halophilic and thermostable MerA ATII-LCL ortholog, the ATII-LCL-NH was much sensitive to heat treatment at 70oC, and is structurally devoid of all the acidic residues (particularly 414DDDD417) and two motifs (432KPAR435 and 465KVGKFP470) that were shown to be involved in the thermostability of the MerA ATII-LCL. Toward rational designing of a MerA enzyme with high thermal stability, the two motifs and the stretch of the four acidic residues, 414DDDD417, were used to substitute their corresponding sequences in ATII-LCL-NH. One mutant in which the stretch of the two acidic amino acids 415DD416 (present in the ATII-LCL) substituted the corresponding amino acids in ATII-LCL-NH was found to be more thermostable than ATII-LCL-NH. However, mutants in which the two motifs were used alone, or in conjunction with 414DDDD417, were extremely unstable to heat treatment. Comparison of the total hydrogen bonds and salt bridges in ATII-LCL-NH and its mutants indicate that a major alteration of the hydrogen bonding occurs in all the mutants that are not stable to heat indicating that subtle structural alteration of the MerA molecule is responsible for the loss of thermostability. The work shows that although structural signature of halophilic proteins could be correlated with the decrease in the hydrophobic contact surface, the bases of thermostability of proteins, judged by the ATII-LCL-NH, are indefinable and do not associate with specific features related to functional amino acids content of the molecule.